Social isolation stress in the early life reduces the severity of colonic inflammation - (:unkn) unknown (My University, 2006)
Objective: To investigate whether the early-life stress interact with a brief stress exposure and acute colonic inflammation in adulthood. Methods: Female Sprague-Dawley rats on the postnatal 21st day were exposed to isolation stress until they reach 250 g. On the last 3 days with or without isolation, water-avoidance-stress (WAS) for 30 min/day or acetic acid(5 %) colitis were performed. After the last WAS or on the 4th day of colitis, rats were decapitated to collect serum for TNF-alpha levels, colonic tissues for histological analysis, myeloperoxidase activity (MPO), evidence of neutrophil infiltration, and glutathione (GSH) levels, a key antioxidant. Results: In the non-isolated and isolated groups, WAS and colitis both elevated the TNF-alpha, MDA levels and MPO activity compared to control (p<0.05-p<0.001). GSH levels were reduced in the non-isolated - WAS or -colitis groups and in the isolated-WAS group (p<0.01-0.001), while GSH level of the isolated-colitis group was not different than control. In the isolated-colitis group, MPO activity and microscopic scores were lower compared to non-isolated group (p<005-0.001). TNF-alpha levels were not different between non-isolated and isolated colitis groups. Conclusion: Post-weaning isolation stress has a protective effect on colonic inflammation and does not exacerbate the colonic response to acute stressors.
Keywords: Colitis; Myeloperoxidase; Psychological stress; Social isolation; Water avoidance stress (WAS)